Capitalism without capital: the intangible economy of education reform. Issue 2 (4th March 2019) - Rowe, Emma
ABSTRACT: This paper explores third-wave post-neoliberalism as an assemblage, fractured and dis/embodied, a mobile tool of governance articulated in various shapes across geopolitical sites. Post-neoliberalism is assembled alongside other key cultural shifts, such as post-truth, posthuman and the computational turn. In light of this Special Issue, this paper will argue that education reform is not only shaped by neoliberal drivers, such as marketisation, competition and decentralisation, but a central tenet of post-neoliberal reform is the presence of the intangible; 'big data' and data-fication, shaped by prominent globalised datasets such as OECD PISA, artificial intelligence, predictive software and complex algorithms. Measurement is far from new in the capitalist economy, but this economy seeks to measure the intangibles, that which does not necessarily exist in three-dimensional spaces. This is, as I will argue in this paper, the mark of capitalism without capital and the rise of the intangible economy in schooling.